Manajemen risiko produksi melon pada sistem greenhouse berbasis pekarangan: Studi kasus Jagotani Farm, Kecamatan Mirit, Kabupaten Kebumen - Agustiana, Dwinita; Merry Anisya, Ayu Putri; Wibisonya, Irawan; Susridar (LP3M Universitas Putra Bangsa, 2025)
Jagotani Farm is a farming business that develops premium melon cultivation in yard land using a semi-automatic drip fertigation greenhouse system. Utilizing yard land as a production site has potential but also faces various risks that can affect yield stability. This study aims to identify melon production risks and formulate risk control strategies. The study was conducted from May to July 2025. The research method used was a case study, with purposive location determination at Jagotani Farm, Mirit District, Kebumen Regency. There were 6 respondent farmers obtained through a census. Data were collected through interviews and observations. Data analysis used the House of Risk (HOR) method and resulted in three priority risk agents and formulated 10 risk mitigation measures based on the level of implementation difficulty and the effectiveness of available resources. Based on the results of this analysis, it is recommended that Jagotani Farm implement production management policies oriented towards risk reduction from the location planning stage. First, it is necessary to establish SOPs for yard land selection. Second, the greenhouse design needs to be adapted to yard conditions through the implementation of adaptive greenhouses. Third, Jagotani Farm needs to develop a crop rotation policy and sanitation intervals between cycles. Fourth, implement an Integrated Pest and Disease Management (PHPT) system. These policies are expected to reduce production risks and improve production stability, fruit quality, and the sustainability of Jagotani Farm's melon farming business going forward.